Molecular biology in medicinal chemistry - T h Dingermann (Wiley-VCH, 2004)
Explains the identification of molecular targets via cellular assays, reporter genes or transgenic models, as well as surveying recent advances in the synthesis, separation and analysis of drugs. A special section is devoted to molecular genetics methods. Appropriate for pharmaceutical chemists, molecular biologists and medical researchers using molecular methods to study drugs and their action.